Aplicabilidade da Lei do Inverso do Quadrado da Dis-tância em radiologia convencional e mamografia - Nathan Willig Lima; Gabriela Hoff (Brazilian Journal of Radiation Sciences, 2015)
The Inverse Square Law (ISL) is a mathematical rule used to adjust the KERMA and exposure to different distances of focal spot having as reference a determined point in space. Taking into account the limitations of this  rule and its application, we have as main objective to verify the applicability of ISL to determine exposure on radiodiagnostic area (maximum tensions between 30kVp and 150kVp). Experimental data was collected, deterministic calculation and simulation using Monte Carlo Method (Geant4 toolkit) were applied to conventional radiology and mammography. The experimental data was collected using a calibrated ionizing chamber TNT 12000 from Fluke. The conventional X-ray equipment used was a Multix Top of Siemens, with Tungsten track and total filtration equivalent to 2.5 mm of aluminum; and the mammographic equipment was a Mammomat Inspiration from Siemens, presenting the track-add filtration combinations of Molybdenum-Molybdenum, Molybdenum-Rhodium, Tungsten-Rhodium. Both equipments have the Quality Control testes in agreement to Brazilian regulations. Based on the results it is possible conclude that the ISL presents lower performance in correct measurements on mammography spectra, i.e. the associated error (differences) achieves a value up to 77.8% and it can cause significant impact on both areas depending on the spectra energy and distance to correct.